Chronic spontaneous urticaria: latest developments in aetiology, diagnosis and therapy. (November 2015) - Vestergaard, Christian; Deleuran, Mette
Chronic urticaria is a debilitating disease characterized by itching and hives with or without angioedema lasting for more than 6 weeks. The disease carries a significant emotional and economic burden for the patient and often results in an odyssey between doctors of different specialities. Patients suffering from chronic urticaria are considered more difficult to satisfy, treat and to have a bigger emotional burden than the average patient in dermatology, paediatric and general practice settings. A joint initiative under the Dermatology section of the European Academy of Allergy and Clinical immunology (EAACI), the Global Allergy and Asthma European Network (GA 2 LEN), the European Dermatology Forum (EDF) and the World Allergy Organization (WAO) has resulted in recently published guidelines for the diagnosis, classification and treatment of chronic urticarial: these guidelines are clinically useful and have a high success rate when followed in daily clinical practice. The treatment of choice for chronic urticaria is still nonsedating antihistamines although other treatments are available, with omalizumab (humanized IgG anti IgE antibodies) as the newest therapy. The pathogenesis of urticaria is poorly understood but autoimmunity is considered as one of the major underlying causes for this disease, although other theories exist.